Karakteristik Pekerjaan, Kewargaorganisasian Dan Kinerja Dosen Universitas Islam Riau - Asril Yusuf; Restu Hayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of job characteristics and organizational citizenhip behavior on the performance of lecturers at the Faculty of Economics and Business, Islamic University. The sample in this study were 40 lecturers at Faculty of Economics and Business UIR. The analytical method used is a structural equation model using SMARTPLS. The results of the study prove that job characteristics and organizational citizenhip behavior have a significant effect on the performance of lecturers at Faculty of Economics and Business Riau Islamic University. Job characteristics are proven to create psychological conditions, namely meaningful work experience, feelings of responsibility for work results, as well as an overview of the actual results of work that will increase internal motivation, job satisfaction and effective work results so that in the end it will improve the final performance of lecturers. . Organizational citizenship behavior has also been proven to create a willingness to cooperate with lecturers at the Faculty of Economics and Business voluntarily even though there is no formal reward system that can ultimately improve their performance. Keywords : Skills, Leadership, Developing Economy, Entrepreneurial Leadership, Indonesian Entrepreneurship